How long-time-to-doctorate PhD candidates persist to earn their degrees - Kohl, Benjamin E. (Kansas State University, 2020)
Research into persistence and attrition of graduate students points to a variety of institutional barriers, individual characteristics, and personal circumstances that contribute to the decision to complete a program or abandon graduate study. Specifically, what is not known is how students who spend a great deal of time in the dissertation phase marshal their resources to successfully complete the degree. This study was intended to help understand the lived experiences of successful doctoral candidates and describe how doctoral candidates who lingered for an extended period in the dissertation phase of their degree program successfully complete their candidacy. The purpose of this study was to examine and describe the lived experiences of three doctoral candidates who earned PhD degrees from Colleges of Education at Midwestern research universities and spent five or more years to successfully complete their dissertations. Of specific interest was how the doctoral candidates made sense of the experiences and made progress to complete their dissertations. This study sought to answer the question: How do long-time-to-doctorate (LTTD) candidates describe the experiences associated with an extended, successful dissertation process? The Interpretative Phenomenological Analysis (IPA) methodological framework of this study guided sampling and participant selection, the research site, data collection methods, interviews, data management, and data analysis. Three LTTD candidates were interviewed and provided their experiences from the time of successfully completing their preliminary examinations to the time they deposited their dissertations. Additional sources of data included a timeline of the dissertation process completed by each participant and the acknowledgements section of two of the participant’s deposited dissertations. These three sources of data provided rich and unique perspectives with similarity in experiences across the participants’ narratives. IPA methods were employed to analyze data including pre-analysis, initial notation, development of emerging themes, identifying gaps, and identifying connections across themes. Although they assumed they were well-prepared for a PhD program, the participants described being surprised by how they struggled throughout their dissertation processes, and in some cases getting stuck in liminality. These times of stuckness and the depth of the liminality they experienced added time to their completion process, in part contributing to their long time to doctoral degree. The participants described strategies and supports they employed to survive the dissertation journey, and in some cases suggested that they wished they had used those strategies sooner. Finally, all of the participants detailed how important completion of the PhD program was to their personal and professional identities, and the way they made meaning about their experiences with faculty involved in the degree completion and identity formation process involved with becoming doctorate. Implications and recommendations for prospective PhD students, academic departments, and graduate schools are discussed.
Keywords: Doctoral; Candidate; Graduate; Education; Persistence; Threshold